Knowledge, attitude, and practice towards thyroid nodules and cancer among patients: a cross-sectional study - Li, Wei; Deng, Jian; Xiong, Wei; Zhong, Yangyan; Cao, Hong; Jiang, Guoqin (Frontiers in Public Health, 2023)
Aim This study aimed to explore the knowledge, attitude, and practice (KAP) towards thyroid nodules (TN) and thyroid cancer (TC) among patients. Subject and methods This cross-sectional study enrolled patients with TN or TC at the Second Affiliated Hospital of the University of South China between September 2022 and February 2023. A self-administered questionnaire was developed to collect demographic information of the participants, and their knowledge, attitude and practice (KAP) towards TN and TC. Results A total of 510 valid questionnaires were collected. Among the participants, 102 (20.00%) were male, and 197 (38.63%) had the diagnosis of TC. The knowledge, attitude and practice scores were 5.76 ± 3.09 (possible range: 0–12), 31.07 ± 2.73 (possible range: 9–45), and 18.97 ± 2.92 (possible range: 5–25), respectively. Multivariate logistic regression showed that age of above 50 years old (OR = 0.27, 95%CI: 0.12–0.64, p = 0.003), junior college or bachelor’s degree and above (OR = 4.97, 95%CI: 1.74–14.20, p = 0.003), monthly income of 5,000–10,000 CNY (OR = 2.02, 95%CI: 1.09–3.74, p = 0.025) and > 10,000 CNY (OR = 5.67, 95%CI: 2.49–12.94, p < 0.001) were independently associated with knowledge. The good knowledge (OR = 3.87, 95%CI: 1.89–7.95, p < 0.001), high school or technical secondary school (OR = 0.52, 95%CI: 0.30–0.88, p = 0.016), and monthly income of 5,000–10,000 CNY (OR = 2.02, 95%CI: 1.13–3.63, p = 0.018) were independently associated with practice. Conclusion Patients demonstrated poor knowledge, moderate attitude, and proactive practice towards TN and TC.